Manajemen Pesantren sebagai Khazanah Tonggak Keberhasilan Pendidikan Islam - Khori, Ahmad (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
Management is one of the most important aspects of managing an institution / agency especially in educational institutions, so expect especially Islamic education institutions and boarding schools because it can not be separated when talking about Islamic education definitely a benchmark of all it is a boarding school education, history has proven that the embryo of formal education is education schools starting from the household, surau, mosques and public places, The new Islam began to grow rapidly after education was started in utakan even serve as doktrinisasi process. Inspirational relentless, berkaryapun always sure, Batsul masa'il, sorogan, mukhadloroh as the hallmark of learning as well as the evaluation process, so as to give birth to a reliable generations who are ready to solve all the problems that occur at this time. Thus the usefulness aspects of Islamic education outcomes can be felt from the ma-society down to the top, this is evidenced by the works of the scholars / clerics and students who continue to fortify themselves with berakhlakul karimah amidst the bustle of the current world developments